Comparison of the efficacy of orthokeratology and highly aspherical lenslets in slowing myopia progression - Chao Li; Fan Yang; WeiFen Gong (Photodiagnosis and Photodynamic Therapy)
Purpose: To evaluate the efficacy of Highly Aspherical Lenslets (HAL) in slowing myopia progression among schoolchildren and compare it to orthokeratology. Methods: This retrospective study included 475 myopic patients aged 6 to 15 years, with myopia ranging from -0.75 to -5.75D Only the right eye of each subject was analyzed. Cycloplegic refraction and axial length(AL) measurements were performed at baseline and after 6 months (only AL measurements were performed in the orthokeratology group after 6 months). Results: After 6 months, HAL lenses(0.00 [-0.25,0.00]D) significantly delayed spherical equivalent refraction (SER) myopia progression compared to single vision (SV) lenses(-0.50 [-0.75,-0.25]D) in both low and moderate myopia(P < 0.001). Additionally, both HAL (0.06 ± 0.10 mm) and orthokeratology(0.04 ± 0.13 mm) lenses significantly reduced AL elongation compared to SV lenses(0.25 ± 0.16 mm, (P < 0.001). However, there was no statistical difference between HAL and orthokeratology lenses in AL elongation(P = 0.157). In the low myopia group, HAL(0.05 ± 0.12 mm) and orthokeratology(0.09 ± 0.15 mm) lenses both significantly slowed AL elongation compared to SV lenses (0.27 ± 0.17 mm, P < 0.001), with HAL lenses showing a slight advantage over orthokeratology lenses(P = 0.038). In the moderate myopia group, both HAL(0.07 ± 0.09 mm) and orthokeratology(0 ± 0.10 mm) lenses significantly delayed AL elongation compared to SV lenses(0.22 ± 0.14 mm), with orthokeratology lenses having a stronger effect than HAL lenses(P < 0.001). Conclusions: HAL lenses demonstrate superior efficacy to SV lenses in mitigating myopia progression in both low and moderate myopia. Both HAL and orthokeratology lenses are effective in reducing AL elongation. Specifically, HAL lenses exhibit greater effectiveness in decreasing AL elongation in cases of low myopia, whereas Ortho-K lenses show a pronounced advantage in managing AL elongation in moderate myopia.